CARDIOVASCULAR RISK IN HIGH SCHOOL TEENAGERS - Vieira Junior, Weder Santana; Oliveira Junior, Francisco; Silva, Marcos de Carvalho e; Oliveira-Silva, Iransé; Venâncio, Patricia Espíndola Mota (International Journal of Movement Science and Rehabilitation, 2021)
The aim of the present study was to identify cardiovascular risks in adolescent high school students at a public school in the city of Anápolis-GO. This is a cross-sectional study of a quantitative character. The population consisted of a total of 567 students of both sexes, randomly selected between the ages of 14 and 17 years. For cardiovascular risks, the Body Mass Index (BMI) was collected; Blood Pressure (BP) and Waist Circumference (WC). Correlation analyzes between variables were performed using the Pearson correlation test and a comparison between classes using the Crosstabs test. The results obtained in the evaluation of the correlation of the variables demonstrated a positive relationship between weight / height, WC / SBP, demonstrating that taller and overweight adolescents are at higher risk for cardiovascular diseases, when a comparison is made between the studied groups. The 1st year was highlighted due to having the largest number of adolescents with BMI, PAD and WC values. It was concluded that adolescents with greater weight and height are more likely to develop cardiovascular diseases and older adolescents may present changes in DBP.